THE ROLE OF SYARIAH COOPERATIVES IN SUPPORTING MICRO-ENTERPRISE FINANCING - Diansyah, Muhamad Rifal; Pangestu, R Ali; Amin, Muhammad (Jurnal Syarikah : Jurnal Ekonomi Islam, 2022)
The aim of this research is to determine the role of the Benteng Micro Indonesia (BMI) sharia cooperative in supporting the financing of micro businesses of members of the Megamendung branch of the BMI sharia cooperative. The research method used is qualitative research with a descriptive approach. The research results show that the Megamendung branch of the BMI sharia cooperative provides productive financing and investment products. Productive financing in additional business capital and investment financing in financing house renovations, financing houses without down payment, financing education and water sanitation. The role of the Megamendung branch of the BMI sharia cooperative is to provide an increase in members’ income after obtaining financing facilities from the Megamendung branch of the BMI sharia cooperative from the previous average income of Rp. 2,075,000 and after financing, namely Rp. 3,175,000 means an increase of 53.02% from income before financing.